Dynamic networks of cortico-muscular interactions in sleep and neurodegenerative disorders - Rizzo, Rossella; Wang, Jilin W. J. L.; DePold Hohler, Anna; Holsapple, James W.; Vaou, Okeanis E.; Ivanov, Plamen Ch. (Frontiers in Network Physiology, 2023)
The brain plays central role in regulating physiological systems, including the skeleto-muscular and locomotor system. Studies of cortico-muscular coordination have primarily focused on associations between movement tasks and dynamics of specific brain waves. However, the brain-muscle functional networks of synchronous coordination among brain waves and muscle activity rhythms that underlie locomotor control remain unknown. Here we address the following fundamental questions: what are the structure and dynamics of cortico-muscular networks; whether specific brain waves are main network mediators in locomotor control; how the hierarchical network organization relates to distinct physiological states under autonomic regulation such as wake, sleep, sleep stages; and how network dynamics are altered with neurodegenerative disorders. We study the interactions between all physiologically relevant brain waves across cortical locations with distinct rhythms in leg and chin muscle activity in healthy and Parkinson’s disease (PD) subjects. Utilizing Network Physiology framework and time delay stability approach, we find that (i) each physiological state is characterized by a unique network of cortico-muscular interactions with specific hierarchical organization and profile of links strength; (ii) particular brain waves play role as main mediators in cortico-muscular interactions during each state; (iii) PD leads to muscle-specific breakdown of cortico-muscular networks, altering the sleep-stage stratification pattern in network connectivity and links strength. In healthy subjects cortico-muscular networks exhibit a pronounced stratification with stronger links during wake and light sleep, and weaker links during REM and deep sleep. In contrast, network interactions reorganize in PD with decline in connectivity and links strength during wake and non-REM sleep, and increase during REM, leading to markedly different stratification with gradual decline in network links strength from wake to REM, light and deep sleep. Further, we find that wake and sleep stages are characterized by specific links strength profiles, which are altered with PD, indicating disruption in the synchronous activity and network communication among brain waves and muscle rhythms. Our findings demonstrate the presence of previously unrecognized functional networks and basic principles of brain control of locomotion, with potential clinical implications for novel network-based biomarkers and early detection of Parkinson's and neurodegenerative disorders, movement, and sleep disorders.